Plan de marketing para la clínica y maternidad sudamericana de la ciudad de Quevedo año 2011 - Coello Montoya, Linda Verónica (2011)
The development of Marketing Plan for the Clinic and Maternity Sudamericana aims to increase its clientele a 25 per cent for the year 2011 improving its position on the market, for obtaining the information is produced two questionnaires with five questions each directed to 396 customers and individuals over 40 years, was also obtained the information primary and secondary education directly to the administrative area. As a result obtained the Clinic at the time does not have any kind of promotion or advertising in some means of communication of the town, and that its brand is not yet defined in the market for health because its corporate image has not been implemented technically. To improve its position on the market has developed a Marketing Plan for the Clinic and Maternity Sudamericana with the aim to make known to the citizenship of Quevedo and its environs services that offer this health center, and that no longer need to travel to other cities to put an end to their health problems. In the Marketing Plan plans were developed promotion and advertising where produced a wedge radial, a video for television, design for the written press, hoarding and flyer. Was supplemented with the redesign of the corporate image: logo and slogan, business cards, triptych, Gigantography, leaves labeled envelopes, white and manilas, adhesives, shining legend, signs of interiors. It was also created two promotions one for customers who attend often and another for the potential customers can go to hear this institution, we must emphasize that the Clinic has an excellent infrastructure to provide good service to customers who visit this health center.